Are preeclampsia and small for gestational age baby could be predicted by placental location? - Singh, Alpana; Vats, Garima; Sharma, Taruna; Shriya, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Objective: Preeclampsia is one of the major cause of maternal and perinatal mortality and morbidity. The pathophysiology is complex and involves multiple organs. The purpose of this study was to find out whether the placental laterality as a predictor of preeclampsia and small for gestational age baby. Methods: This was prospective observational study conducted from February 2015 to December 2015, in a tertiary care hospital of Delhi. 347 antenatal patients attending obstetrics OPD without high risk factors were enrolled. After enrolment 50 patients were lost to follow up and 27 not delivered in our hospital. Ultrasonography for placental localization was done at 18-24 weeks of pregnancy. Patients were followed till delivery for pregnancy outcomes such as preeclampsia, small for gestation age (SGA) baby and mode of delivery. Placenta locations were divided into lateral (either right or left) and central (anterior, posterior or fundal). Results: Out of 347, a total of 270 patients were analysed, 39 (14.4%) had lateral placenta and among them 17 (43.5%) developed preeclampsia and 24 (61.5%) had small for gestational age baby (p<0.001). 231 (85.5%) had central placenta and among them 49 (21.2%) developed preeclampsia and 63 (27.2%) had small for gestational age baby (p <0.001). Conclusions: Laterally located placenta had significant association with preeclampsia and small for gestational age babies.